Effect of Digital Age on the Transmission of Cultural Values in Product Design - Cakmakcioglu, Betul Aybala (Routledge Journals, Taylor & Francis Ltd, 2017)
In today's world, contemporary trends and changes that emerged from technological developments transform the ways of cultural transmissions. New abilities gained from the digital technologies are changing cultural values and their formation process. Cultural and traditional values mostly took form through craft in the history but now they are produced by new modern techniques like rapid prototyping and reforming. In this study, the ways of transmitting cultural elements to digital age is handled by analyzing the sample products that contain cultural signs and produced or designed by post-industrial techniques and affected by digital age trends. The research is conducted by; firstly, summarizing the data that is gathered from literature review, then evaluating the findings that are gained from product analysis and observation. Consequently, the methods for transferring culture to the future in scope of product design and the interactive relation between cultural object design and technology are presented and discussed.
12th International Conference of the European-Academy-of-Design (EAD) -- APR 12-14, 2017 -- Sapienza Univ Rome, Fac Architecture, Rome, ITALY
Keywords: Cultural transmission; Product design; Digital age; Technology